2019
DOI: 10.1016/j.jtbi.2019.07.019
|View full text |Cite
|
Sign up to set email alerts
|

A stochastic individual-based model to explore the role of spatial interactions and antigen recognition in the immune response against solid tumours

Abstract: Spatial interactions between cancer and immune cells, as well as the recognition of tumour antigens by cells of the immune system, play a key role in the immune response against solid tumours. The existing mathematical models generally focus only on one of these key aspects. We present here a spatial stochastic individual-based model that explicitly captures antigen expression and recognition. In our model, each cancer cell is characterised by an antigen profile which can change over time due to either epimuta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 106 publications
(136 reference statements)
0
19
0
Order By: Relevance
“…In particular, neoantigen-related subclonal death takes into account antigen load and frequency across the tumour while keeping the number of model parameters small. Our framework contemplates computational methods and data in both epitope immunogenicity [17] and immune search efficiency [18,29,30] to translate previous evidence into a mathematical model able to produce insight into the underlying subclonal dynamics. Analytical results of the new model indicate that a heterogeneity threshold separates cancer growth from immune control, so that highly heterogeneous neoantigen landscapes might impair immune efficiency.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, neoantigen-related subclonal death takes into account antigen load and frequency across the tumour while keeping the number of model parameters small. Our framework contemplates computational methods and data in both epitope immunogenicity [17] and immune search efficiency [18,29,30] to translate previous evidence into a mathematical model able to produce insight into the underlying subclonal dynamics. Analytical results of the new model indicate that a heterogeneity threshold separates cancer growth from immune control, so that highly heterogeneous neoantigen landscapes might impair immune efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…We postulate that a higher antigen load increases the probability of presenting more immunogenic epitopes, thus increasing subclonal dominance D. Additionally, it has been shown that even highly recognizable antigens fail at inducing a T cell response if they are not present in a sufficient fraction of the tumour [14,15]. Following research on immune search mechanisms [18,29,30], we hypothesize that increased epitope heterogeneity leading to more private antigens will result in a loss of T cell efficiency E.…”
Section: Mathematical Framework 21 Neoantigen Heterogeneity and The Cancer-immune Ecologymentioning
confidence: 98%
See 1 more Smart Citation
“…A spatial model for the cancer-immune interaction has been recently proposed in [28], where T cells walk on a twodimensional grid in search for antigens. Here, we present a similar model able to explicitly compute the dependency of T cell search efficiency on antigen clonality.…”
Section: Immune Search Efficiency Ementioning
confidence: 99%
“…Spatial structure in biological populations includes both clustering and segregation [32][33][34][35][36][37]. Stochastic individual-based models (IBM) offer a straightforward means of exploring population dynamics without invoking a meanfield approximation [38,39]. However, IBM approaches are computationally prohibitive for large populations and provide limited mathematical insight into the population dynamics, for example how particular biological mechanisms affect the carrying capacity or the Allee threshold [40].…”
Section: Introductionmentioning
confidence: 99%